Phenotypic and molecular characterization of multidrug-resistant Salmonella enterica serovar Hadar in Greece, from 2007 to 2010. (February 2015) - Papadopoulos, T.; Petridou, E.; Zdragas, A.; Nair, S.; Peters, T.; de Pinna, E.; Mandilara, G.; Passiotou, M.; Vatopoulos, A.
Abstract: All 120 strains of Salmonella enterica serovar Hadar isolated during 2007–2010 in Greece were characterized by phenotypic and molecular methods. High rates of resistance to nalidixic acid (92%) and low levels of ciprofloxacin resistance (88%) were observed. Pulsenet-pulsed field gel electrophoresis profile SHADXB.0001 was predominant in Greece (58%) as in Europe but PT1, a rare phage type in Europe, was frequent in Greece (56%). The SHADXB.0001 and PT1 clone (38%) were found in humans, animals and food of animal origin with R-type ApSpTNxpCp being predominant (25%). The data indicate that this clone (possibly endemic) was circulating through the food chain in Greece during the study period.